The rising threat of intrinsically resistant Candida species in Argentina - Garcia, Guillermo Manuel (2023)
In recent years, the medical community has faced a growing concern: the emergence of Candida species that exhibit intrinsic resistance to commonly used antifungal drugs. This alarming trend poses a significant challenge in the management of fungal infections and demands immediate attention and action. In this editorial, we shed light on the implications of intrinsic resistance in Candida species and emphasize the urgent need for enhanced strategies to combat this threat.